PENGARUH PENDIDIKAN KESEHATAN MEDIA BOOKLET TERHADAP PENGETAHUAN KELUARGA DALAM PERAWATAN LUKA DIABETES MELLITUS - Ari Wiryansyah, Oscar; Marlina, Leni (Jurnal Kesehatan dan Pembangunan, 2025)
Diabetic ulcers are severe complications of diabetes mellitus that require rapid treatment because they can lead to dangerous conditions. One way that can be taken to improve family understanding in carrying out wound care in diabetic patients is by providing health education through booklet media. This study aims to identify the impact of providing health education using booklet media on increasing family knowledge in wound care in diabetic patients. The method used is pre-experimental with a pre- post test approach using a one group pretest-posttest design. The subjects in this study were families who had members with wounds due to diabetes mellitus. A total of 50 respondents were sampled using the total sampling method. The measuring instrument used was a questionnaire to assess the level of knowledge of respondents, and booklet media as a means of providing education. The findings of the study indicated an increase in the level of family knowledge after receiving health education, namely from 62% to 70%. The results of statistical analysis using the Wilcoxon test showed a p value of 0.000 (p <0.05), which indicates that the use of booklet media has a significant effect on increasing family knowledge in treating diabetic wounds. The researchers suggest that further research can examine other, more diverse variables with different methodological approaches.